Azole-resistant Aspergillus fumigatus harboring the TR34/L98H mutation : first report in Portugal in environmental samples - Gonçalves, Paulo (2021)
Copyright: © 2020 by the authors. Licensee MDPI, Basel, Switzerland. This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY) license (https://creativecommons.org/licenses/by/4.0/).